Effect of cisplatin/gold chitosan nanocomposite on oral squamous cell carcinoma and oral epithelial cells - Basma Abdelrahman Ahmed; Rania Osama M. Mohsen; Marwa Sharaky; Marwa A. Ramadan; Amna H. Faid; Mai Hafez Mohamed (Cancer Nanotechnology)
Abstract Background Oral squamous cell carcinoma (OSCC) treatment represents a great challenge, since platinum-based therapeutic agents have deleterious effects on normal cells and tissues. Employing gold nanoparticles (AuNps) as carriers for cisplatin have proved effective in reducing cisplatin doses. Green synthesis of AuNps from eco-friendly agents like chitosan improves the AuNps’ biocompatibility and cytotoxicity. Thus, we synthesized a novel agent of cisplatin coupled to gold chitosan nanoparticles (Cis/AuCh nanocomposite) and examined its effect in addition to the effect of chitosan-reduced gold nanoparticles (AuCh Nps) on (HNO97) OSCC cell line and normal oral epithelial cells (OEC). Results Ultraviolet–visible spectroscopic analysis, transmission electron microscope, X-ray diffraction, and Fourier transform infrared spectroscopy confirmed the successful synthesis of AuCh Nps and Cis/AuCh nanocomposite. The cytotoxicity assay showed that the IC50 doses of AuCh Nps and Cis/AuCh nanocomposite after 48 h were 12.5 μg/ml, and 6.2 μg/ml, respectively, on the HNO97 cell line. On the other hand, the IC50 doses were 40 μg/ml and 44.5 μg/ml on OEC, respectively. After treating both cell lines with the HNO97–IC50 doses, Cis/AuCh nanocomposite-treated HNO97 cell line revealed a significant rise in Caspase 3 immunohistochemical apoptotic index, besides a significant elevation in pro-apoptotic proteins and reduction in Bcl-2 compared to cisplatin. Conversely, opposite results were detected in AuCh Nps and Cis/AuCh nanocomposite-treated OEC. Flow cytometry results revealed S and G2/M shifts in HNO97 and OEC with more shift in the cisplatin-treated group than AuCh Nps and Cis/AuCh nanocomposite-treated groups in both cell lines. The expressions of the reactive oxygen species (ROS) markers; malondialdehyde and nitric oxide were the highest in Cis/AuCh nanocomposite-treated HNO97, while the reduced glutathione expression was the lowest. However, AuCh Nps and Cis/AuCh nanocomposite-treated groups did not display any significant changes in ROS markers expression from the untreated group in the OEC. Conclusions AuCh NPs can be considered a good alternative way of cisplatin transportation for OSCC treatment. Cis/AuCh nanocomposite stimulates apoptosis, cell cycle arrest, and ROS production in oral cancer cells with less undesired effects on normal oral epithelial cells.